2016
DOI: 10.1111/jocn.13256
|View full text |Cite
|
Sign up to set email alerts
|

‘Close to’ a palliative approach: nurses' and care aides' descriptions of caring for people with advancing chronic life‐limiting conditions

Abstract: Nurses care for people with advancing chronic life-limiting conditions in a variety of settings who would benefit from a palliative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 32 publications
4
28
0
2
Order By: Relevance
“…The scoping review demonstrates a perceived lack of respect for the role of UCPs by other healthcare providers and a lack of authority for decision‐making in patient care. This theme was consistent across Canada, with studies from British Columbia (Reimer‐Kirkham, Sawatzky, Roberts, Cochrane, & Stajduhar, ), Alberta (Dahlke & Baumbusch, ; White, Jackson, Besner, & Norris, ), Ontario (Giosa et al., ; Heckman et al., ; Kaasalainen et al., ; Kontos, Miller, & Mitchell, ; McGilton, Guruge, Librado, Bloch, & Boscart, ; Tayab & Narushima, ; Wagner et al., ; Zeytinoglu et al., ) and New Brunswick (McCloskey, Donovan, Stewart, & Donovan, ; Rheaume, ) reporting minimal UCP contribution to interprofessional care teams and highlighting important challenges. Such challenges included vertical power hierarchies within the teams (Heckman et al., ; McGilton et al., ), isolation from teams or lack of communication and collaboration between UCPs and other members of the team (Dahlke & Baumbusch, ; Heckman et al., ; Tayab & Narushima, ), lack of role clarity and perceived differences in knowledge among team members (Heckman et al., ; Reimer‐Kirkham et al., ) and a limited role in documentation in patient charts (Kontos et al., ; McCloskey et al., ; White et al., ).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The scoping review demonstrates a perceived lack of respect for the role of UCPs by other healthcare providers and a lack of authority for decision‐making in patient care. This theme was consistent across Canada, with studies from British Columbia (Reimer‐Kirkham, Sawatzky, Roberts, Cochrane, & Stajduhar, ), Alberta (Dahlke & Baumbusch, ; White, Jackson, Besner, & Norris, ), Ontario (Giosa et al., ; Heckman et al., ; Kaasalainen et al., ; Kontos, Miller, & Mitchell, ; McGilton, Guruge, Librado, Bloch, & Boscart, ; Tayab & Narushima, ; Wagner et al., ; Zeytinoglu et al., ) and New Brunswick (McCloskey, Donovan, Stewart, & Donovan, ; Rheaume, ) reporting minimal UCP contribution to interprofessional care teams and highlighting important challenges. Such challenges included vertical power hierarchies within the teams (Heckman et al., ; McGilton et al., ), isolation from teams or lack of communication and collaboration between UCPs and other members of the team (Dahlke & Baumbusch, ; Heckman et al., ; Tayab & Narushima, ), lack of role clarity and perceived differences in knowledge among team members (Heckman et al., ; Reimer‐Kirkham et al., ) and a limited role in documentation in patient charts (Kontos et al., ; McCloskey et al., ; White et al., ).…”
Section: Resultssupporting
confidence: 63%
“…Such challenges included vertical power hierarchies within the teams (Heckman et al., ; McGilton et al., ), isolation from teams or lack of communication and collaboration between UCPs and other members of the team (Dahlke & Baumbusch, ; Heckman et al., ; Tayab & Narushima, ), lack of role clarity and perceived differences in knowledge among team members (Heckman et al., ; Reimer‐Kirkham et al., ) and a limited role in documentation in patient charts (Kontos et al., ; McCloskey et al., ; White et al., ). Such challenges lead to a lack of confidence among UCPs as they provide care for patients (Reimer‐Kirkham et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the consultant structure had the potential to affect the palliative care practices at an interpersonal level that may have had negative patient consequences, such as reduced quality of life during patients' last days. In fact, the practices of the consultant organization may directly contradict palliative care guidelines, especially when ANs' roles and relationships with RNs are varied and nonstandardized (Juthberg & Sundin, ; Reimer‐Kirkham et al., ). Previous studies have shown that ANs in RCFs are especially dependent on RN support in palliative care situations (Juthberg & Sundin, ; Karlsson, Ekman, & Fagerberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…Often, RNs delegate the responsibility of giving medication to ANs when needed, such as when older patients are in pain. Several studies have underlined the need to improve the education of ANs in palliative care, particularly in the RCF setting (Eriksson, Bergstedt, & Melin-Johansson, 2015;Reimer-Kirkham, Sawatzky, Roberts, Cochrane, & Stajduhar, 2016;Ronaldson, Hayes, Carey, & Aggar, 2008), as one way to strengthen the professional care given by ANs (Daly & Szebehely, 2012). The National Board of Health and Welfare (2011) emphasized that staff involved in elderly care must be skilled and experienced.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation